Kaempferol: A flavonoid with wider biological activities and its applications - Bangar, Sneh Punia; Chaudhary, Vandana; Sharma, Nitya; Bansal, Vasudha; Ozogul, Fatih; Lorenzo, Jose M. (Critical reviews in food science and nutrition, 2023)
Kaempferol and its derivatives are naturally occurring phytochemicals with promising bioactivities. This flavonol can reduce the lipid oxidation in the human body, prevent the organs and cell structure from deterioration and protect their functional integrity. This review has extensively highlighted the antioxidant, antimicrobial, anticancer, neuroprotective, and hepatoprotective activity of kaempferol. However, poor water solubility and low bioavailability of kaempferol greatly limit its applications. The utilization of advanced delivery systems can improve its stability, efficacy, and bioavailability. This is the first review that aimed to comprehensively collate some of the vital information published on biosynthesis, mechanism of action, bioactivities, bioavailability, and toxicological potential of kaempferol. Besides, it provides insights into the future direction on the improvement of bioavailability of kaempferol for wide applications.